1968
DOI: 10.1161/01.res.23.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic Innervation of the Developing Rabbit Heart

Abstract: The sympathetic innervation of the rabbit heart, as a function of age, was studied by measuring the cardiac concentration of catecholamines and observing the anatomic distribution of sympathetic nerves by die monoamine fluorescense technique. The cardiac concentration of norepinephrine in late gestation was quite low; the levels rose progressively after birth to reach adult levels by about three weeks of age. Similar small amounts of epinephrine were found in the hearts at all ages. Substantially less change i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
34
0
1

Year Published

1969
1969
2005
2005

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(39 citation statements)
references
References 2 publications
4
34
0
1
Order By: Relevance
“…Findings obtained in the present study that content of noradrenaline in rabbit ventricles increased significantly with development from day 2 to day 30 are quite consistent with the result seen in rabbit whole hearts (5). In addition to increasing the accumulating ability of noradrenaline in adrenergic nerves (14,15), the nerve density in the myocardial wall may also increase with development of the heart.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Findings obtained in the present study that content of noradrenaline in rabbit ventricles increased significantly with development from day 2 to day 30 are quite consistent with the result seen in rabbit whole hearts (5). In addition to increasing the accumulating ability of noradrenaline in adrenergic nerves (14,15), the nerve density in the myocardial wall may also increase with development of the heart.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to increasing the accumulating ability of noradrenaline in adrenergic nerves (14,15), the nerve density in the myocardial wall may also increase with development of the heart. In their fluorescence histochemical study, Friedman et al (5) suggested that a significant proportion of noradrenaline measured in the newborn heart resides in the preterminal nerve trunks and therefore may not be in close anatomical proximity to adrenergic receptors in the myocardial cell. In the present study, however, the response to tyramine was not appreciably altered with development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of this relative lack of sympathetic innervation, ventricular myocardial levels of norepinephrine are reduced in the young animal (6). It follows, therefore, that decreased responsiveness of neonatal myocardial tissue to agents that act in part by releasing norepinephrine would be expected.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, newborn rabbit hearts have low epinephrine stores and decreased sympathetic innervation. 28 Because the newborn has an immature conduction system and sympathetic innervation she may be susceptible to toxicity even from accepted therapeutic doses of lidocaine. Indeed, foetal hearts bathed with therapeutic levels of amide local anaesthetic solutions demonstrate a decreased spontaneous contraction rate and increased A-V conduction times.…”
Section: Discussionmentioning
confidence: 99%